Peningkatan pemahaman PSAk 69: Pendekatan Case Based Reasoning - Arum Prastiwi; Nurlita Novianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
All institutions must have a financial management which a financial management is necessary to carry out internal and external controls. External financial control of an entity is carried out by Public Accountant. This control usually focuses on examining the financial statements that are the entity's financial accountability reports to their owners. In conducting the audit, the Public Accountant needs to understand the entity's business processes in order to find out the truth of the data reported in the financial statements. At current time the agricultural industry is growing rapidly because the government continues to optimize agriculture. Malang is one of the areas with many agricultural and plantation industries. Public Accountant firm “X” who are community service partners are in Malang. The Public Accountant requires training and assistance on PSAK 69 related to agriculture. This needs to be done because Public Aacountant is surrounded by many agiculture industries. The method used in this service is Case Based Reasoning. The results of this training are that there are 12 human resources of KAP